The Hunter's Code - Jake Maddox (Stone Arch Books, 2009)
For as long as he can remember, Ethan has envied his dad's hunting trips. His dad has always promised to bring Ethan along when he's old enough, and finally, this year is the year! But on their hunt, Ethan discovers some dead deer left in the woods. A poacher is killing the animals for fun. Ethan knows that's against the Hunter's Code . . . after all, he broke that rule himself.
Keywords: Sport Stories -- Sport Stories